Development and Implementation of a Web-Based Village Information System to Optimize Services - Fahad Rizki; Nugraha Nugraha; Zaenal Alamsyah (bit-Tech, 2025)
Batununggal Village faces persistent challenges in administrative services, including manual processes that cause delays, inefficiencies, and limited access to information. This study develops a web-based village information system designed to optimize these services through the Prototype method. The system integrates React.js for the frontend, Laravel for the backend, and MySQL for the database, forming a scalable and user-friendly architecture. Unlike previous studies that focused only on basic services, the proposed system introduces a more comprehensive model by combining online letter submission, resident data management, UMKM promotion, transparent APBDes reporting, and citizen complaint channels.The Prototype method was applied iteratively, allowing continuous refinement based on feedback from both residents and village staff. System testing employed black-box evaluation, confirming that all features functioned as expected. Furthermore, user satisfaction was measured through a Likert-scale questionnaire distributed to 31 residents, resulting in an overall score of 81.55%, categorized as “Agree.” Similarly, evaluations from 10 village staff indicated that 70–80% found the system very helpful in supporting their tasks. These findings demonstrate that the system improves service efficiency, increases transparency, and enhances community participation in governance. In addition to addressing long-standing service issues in Batununggal Village, the system provides a replicable model for other rural communities. Future development will prioritize the integration of automated notifications and a mobile application to broaden accessibility and ensure long-term adoption.